2017
DOI: 10.1039/c6ew00211k
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigators series: building a theory for smart stormwater systems

Abstract: Smart stormwater systems will transform cities into coordinated and real-time controlled treatment plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Detention pond with fixed outflow is a, "stationary solution to this highly dynamic rainfall-runoff problem" (Mullapudi et al, 2017). Consequently, this traditional detention/retention basin practices are static and poorly equipped to adapt to the continuously changing climate and land use (Mullapudi et al, 2017). As a result, adaptive stormwater management strategies are required for resilient and robust of urban stormwater infrastructure.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Detention pond with fixed outflow is a, "stationary solution to this highly dynamic rainfall-runoff problem" (Mullapudi et al, 2017). Consequently, this traditional detention/retention basin practices are static and poorly equipped to adapt to the continuously changing climate and land use (Mullapudi et al, 2017). As a result, adaptive stormwater management strategies are required for resilient and robust of urban stormwater infrastructure.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Wong and Kerkez, (2018) reduced the engineered watershed storage volume up to 50% by actively controlling 4 detention ponds depending on their hydraulics. Mullapudi et al, (2017) showed three ponds and a treatment wetland can be controlled simultaneously to reduce downstream flood risk also getting 46.48% nitrate load reduction.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For the regulation of the gates before and during floods, the management stakeholders must establish optimal real-time operations, because the long-term approach cannot be used, due to the short timeframe of the new course of the torrent. Some modeling techniques used in a real-time control can be adopted to adjust the operations when facing single precipitation events [44].…”
Section: Datementioning
confidence: 99%
“…While these functions were previously achieved only through construction of static gray infrastructure or centralized treatment facilities, the addition of remotely-controlled valves and pumps promises to realize the same benefits while at the same time reducing costs, expanding coverage, and allowing system performance to scale flexibly with changing hydrologic conditions. Adding valves to existing stormwater facilities, for instance, can extend hydraulic retention time, thereby promoting the capture of sediment-bound pollutants [19], [20]. Modulation of flows (hydrograph shaping) may reduce erosion at downstream locations by ensuring that discharges do not exceed critical levels [19].…”
Section: A Motivationmentioning
confidence: 99%